Value Orientation Towards Reproductive Health Behavior Among Muslim Women: A Sociological Analysis - Pravin, Saba; Kumar, Alok; Kumari, Prita; Rathi, Akash (Journal of Neonatal Surgery, 2025)
This study examines how cultural and religious value orientations influence reproductive health behaviors among Muslim women in Jansath town, located in the Muzaffarnagar district of Western Uttar Pradesh, India. In the context of deeply rooted patriarchal norms and religious beliefs, reproductive health decisions are often influenced by various socio-cultural factors. The aim of this study is to explore the impact of these factors on family planning practices, with a focus on contraceptive use and decision-making within Muslim households. Data were collected from a purposively selected sample of 400 Muslim women through an interview schedule and observation techniques. The findings reveal that reproductive decisions are largely influenced by male partners, with many respondents reporting that their husbands take the primary initiative in determining the number of children. Religious beliefs emerged as a significant factor, with a majority of women considering the use of contraception to be sinful and inconsistent with their faith. However, some women reported using contraceptives specifically for child spacing rather than limiting family size. These outcomes reflect the continuing impact of patriarchal norms, gendered decision-making, and religious interpretations on women’s autonomy in reproductive health within the socio-cultural context of their communities.